Reaction synthesis of porous nano-structured mullite ceramic composites from alumina and zeolite-poor rock with enhanced strength and low thermal conductivity - Jamal Eldin F.M. Ibrahim; Emese Kurovics; Mohammed Tihtih; Mohamed A. Basyooni; István Kocserha (Results in Engineering, 2023)
Porous mullite-based ceramics have been developed using a mixture of zeolite-poor rock and alumina through mechanical activation and reactive sintering. The experimental findings demonstrate that the in-situ mullite growth may develop in a variety of shapes, including whiskers, nanofiber, nanonetwork and diamond-like particles. The XRD examination indicates that the samples sintered at 1500 °C are mostly made of the mullite phase. The SEM photographs show that as the sintering temperature increases, the mullitization process takes place first in zeolite-poor rock particles, and subsequently, alumina combines with the silica-containing phase via a liquid-phase sintering mechanism to produce an interlocking network of extended secondary mullite. The effects of mullite formation and the sintering temperature on various properties of the sintered samples, such as their density, apparent porosity, thermal conductivity, strength, wear resistance, composition, morphologies, and microstructural characteristics of the sintered samples were studied. Increasing the sintering temperature from 1100 to 1500 °C improved the different properties. The density increased from 1.9 to 2.1 g/cm3, thermal conductivity rose from 0.9 to 1.6 W/m.K, compressive strength escalated from 18.9 to 92.1 MPa, and worn material volume decreased from 2444 to 36.9 mm3 after a 5-min abrasion test.